Defining a murine ovarian cancer model for the evaluation of conditionally-replicative adenovirus (CRAd) virotherapy agents - Rebeca González-Pastor; Ahmad Mohammad Ashshi; Adel Galal El-Shemi; Igor P. Dmitriev; Elena A. Kashentseva; Zhi Hong Lu; S. Peter Goedegebuure; Osvaldo L. Podhajcer; David T. Curiel (BMC, 2019)
Abstract Background Virotherapy represents a promising approach for ovarian cancer. In this regard, conditionally replicative adenovirus (CRAd) has been translated to the context of human clinical trials. Advanced design of CRAds has sought to exploit their capacity to induce anti-tumor immunization by configuring immunoregulatory molecule within the CRAd genome. Unfortunately, employed murine xenograft models do not allow full analysis of the immunologic activity linked to CRAd replication. Results We developed CRAds based on the Ad5/3-Delta24 design encoding cytokines. Whereas the encoded cytokines did not impact adversely CRAd-induced oncolysis in vitro, no gain in anti-tumor activity was noted in immune-incompetent murine models with human ovarian cancer xenografts. On this basis, we explored the potential utility of the murine syngeneic immunocompetent ID8 ovarian cancer model. Of note, the ID8 murine ovarian cancer cell lines exhibited CRAd-mediated cytolysis. The use of this model now enables the rational design of oncolytic agents to achieve anti-tumor immunotherapy. Conclusions Limits of widely employed murine xenograft models of ovarian cancer limit their utility for design and study of armed CRAd virotherapy agents. The ID8 model exhibited CRAd-induced oncolysis. This feature predicate its potential utility for the study of CRAd-based virotherapy agents.